Aesthetic Dermatology, The Rising Trend - Uma Keyal; Deeptara Pathak Thapa (Nepal Journal of Dermatology, Venereology & Leprology)
Aesthetic Dermatology, also known as cosmetic dermatology provides treatment for skin, hair or body that emphasizes on improving an individual’s appearance. It is widely conducted to treat conditions such as moles, wrinkles, scars, excess fat, skin discoloration, skin laxity, and cellulite. Benefits such as minimally invasive or non-invasive and relatively less time-consumption with better outcomes has foster the patients to seek these treatments. With soaring demand for these treatments, numerous myths and misconceptions regarding the field of aesthetic dermatology have arisen which need to addressed. Also, this constantly evolving field with new devices and tools requires extra vigilance, continue medical education and a governing body to have check upon negligent professional activity, if occurs any